ANALISIS SISTEM PEMBUMIAN TOWER SALURAN TRANSMISI DARI GARDU INDUK KAPAL – GARDU INDUK GIANYAR - IGP Agung Satya Wicaksana; IW Arta Wijaya; IGN Janardana (Program Studi Teknik Elektro UNUD, 2021)
This study aims to improve the earthing value of transmission lines which have an earthvalue less than the standard value off SPLN No 121: 1996, namely 10 and recommend anearthing system that meets the standards. Theemethodduseddissa descriptive method bycalculating the value of the earthing system by following the SPLN standard No. 121: 1996. Thisanalysis consists of several stages, namely a site survey, measuring soil resistance (R) tocalculate the value of soil resistivity (?) then calculating the value of grounding resistance with 5types of grounding systems to achieve grounding resistance 10 , namely one electrodegrounding system, 2 electrode grounding system planted vertically S > L, 2 electrode earthingsystem planted vertically S < L, plate earthing system, and a grid-rod earthing system. Theresults of the research are for paddy fields using a vertical one-electrode earthing system, thevalue is 7.32 ? with a manufacturing cost of Rp. 857,000, on farmland with a vertical oneelectrodeearthing system, the value is 8.36 ? with a manufacturing cost of Rp. 1,363,000, andon clay soil with a vertical one-electrode earthing system, the result is 7.98 ? with amanufacturing cost of Rp. 857,000.